2013
DOI: 10.4028/www.scientific.net/kem.549.84
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography from Single Point Incremental Forming Using an Acetal Tool

Abstract: This paper investigates a new tool, where the forming tip is constructed from acetal. The acetal tip is investigated because it is self-lubricating and more compliant than traditional SPIF tools. This work characterizes the topography of surfaces created by forming aluminum with both the acetal-tipped tool and a carbide tool. When the parts are compared visually, the parts formed with the acetal tool maintain the appearance of the unformed sheet metal. The surfaces of the parts are measured using an Olympus LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…As observed by Ham et al [13] earlier, the orange peel effect can be attributed to the grain size and lattice structure. On subjecting the sheet to heat treatment, the increase in grain size results in an outer surface that has a reduced average surface roughness but higher anisotropy on forming.…”
Section: Underlying Physical Principles: Discussion and Recommendationssupporting
confidence: 52%
See 1 more Smart Citation
“…As observed by Ham et al [13] earlier, the orange peel effect can be attributed to the grain size and lattice structure. On subjecting the sheet to heat treatment, the increase in grain size results in an outer surface that has a reduced average surface roughness but higher anisotropy on forming.…”
Section: Underlying Physical Principles: Discussion and Recommendationssupporting
confidence: 52%
“…It was also shown that SPIF could be done at high speeds, as a result of this work. Later, Ham et al [13,14] suggested that it was more useful to use areal surface texture parameters in evaluating surface texture and topography in SPIF and compared surfaces produced using two different types of tools, acetal, and carbide. It was found that the acetal tool produces rougher surfaces than the carbide tool, but with more isotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some researchers tried to select the most suitable material and tool diameter to get a better surface finish. Ham et al [84] used two tools: one was acetal tipped, and the other was a carbide tool to characterize the topography of surfaces created by forming aluminium sheet. It was found that the Fig.…”
Section: Tool Size and Materialsmentioning
confidence: 99%
“…The main standard 3D parameters determined by this measurement are the average roughness Sa, the highest peak of the surface Sp, the root mean square roughness parameter Sq, and the maximum pit depth Sv. Selection of surface roughness parameters was based on the work of Ham et al [32,33] which suggested that it was more useful to use areal surface texture parameters in evaluating surface texture and topography in single point incremental sheet forming.…”
Section: Surface Characterisationmentioning
confidence: 99%